ANALISIS KUALITATIF FENILALANIN SECARA CHROMATOGRAPHY KERTAS DAN CHROMATOGRAPHY LAPIS TIPIS (Studi Awal Pengembangan Metode Deteksi Penyakit Phenylketonuria) - Begum Fauziyah (SAINSTIS, 2012)
The qualitative analysis of fenilalanin as paper chromatography and thin layer chromatography is developed as the beginning study of detection phenylketonuria  disease.  The  result  of  identification  qualitatively fenilalanin     solution     with     concentration     varia tion     using     paper chromatography media shows that the clearest spot is gotten by concentration minimal 50 ppm. The result of identification qualitatively fenilalanin  solution  with  variation  concentration  1,  3,  5,  10,  25  and  50 (ppm) using thin layer chromatography shows that from the smallest concentration  that  is  1  ppm,  has  already  give  the  clear  qualitative experiment result, that is purple. Fenilalanin analysis with thin layer chromatography gives more sensitive result than with paper chromatography. memberikan hasil yang lebih sensitif daripada dengan chromatography kertas.